2019
DOI: 10.5005/jp-journals-10048-0047
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Thermomechanically Heat-treated Nickel–Titanium Alloy Used in Endodontics

Abstract: The use of nickel-titanium (NiTi) alloys created a revolutionary impact in endodontic treatments. Shape memory and superelastic property of an NiTi alloy make the instrument more flexible, which improves the quality of the treatment by reducing the procedural errors. Even though these instruments show advanced metallurgical properties, it can lead to fracture due to fatigability. To improve the fracture resistance and enhance the clinical performance, various thermomechanical heat treatments had been introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Since the Ni‐Ti file was first introduced in the endodontic field by Walia [18], it has been widely used because of its superelasticity and flexibility [6]. Recently introduced heat‐treated Ni‐Ti instruments have shown improved fracture resistance and mechanical properties and have been used frequently [7]. However, we found only one study that reported the accuracy of EALs with heat‐treated Ni‐Ti files [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the Ni‐Ti file was first introduced in the endodontic field by Walia [18], it has been widely used because of its superelasticity and flexibility [6]. Recently introduced heat‐treated Ni‐Ti instruments have shown improved fracture resistance and mechanical properties and have been used frequently [7]. However, we found only one study that reported the accuracy of EALs with heat‐treated Ni‐Ti files [11].…”
Section: Discussionmentioning
confidence: 99%
“…If the temperature is above the austenitic finish (Af) temperature, the alloy exists in an austenitic state. Upon cooling, if the temperature is below the martensitic finish temperature (Mf), the alloy exists in the martensitic phase [7]. For example, the Af temperature of ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland) is approximately 15°C and it exists in an austenitic state at room temperature [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation